OPTIMIZATION OF REMOTE CONTROL OF MEASUREMENT RESULTS THROUGH A MANIPULATOR (Web of Technology: Multidimensional Research Journal, 2024)
It is aimed at optimizing remote control of manipulators based on measurement results in automated systems. As the use of robotic systems in various industries is increasing, precise control of robotic manipulators is essential to achieve high precision and efficiency. Learns how to use optimization algorithms such as Gradient Descent, Genetic Algorithms, and Kalman Filtering to adjust manipulator movements based on feedback from measurement systems.